Diseases of the ocular system diagnosed in dogs and cats from Havana, Cuba. Period 2014-2020 - Hugues, Beatriz (2022)
In Cuba, a study was carried out on diseases of the ocular system in dogs and cats in the period 2000-2013 in the specialized ophthalmology clinic of the main veterinary clinic in Havana, Cuba. Based on these results, the objective of this work was to describe the frequency of these eye diseases in the period 2014 to 2020. The sample was made up of 3186 dogs and 177 domestic cats (n=3363), which was stratified by breed, sexes, and ages. In dogs, it was determined that Pekingese breed (2070; 65%), females (1820; 57%) and animals between 1-5 years (1413; 44%) and 6 or more years (977; 31%) were the most affected. Conditions of the lacrimal system (69%), cornea (10%), eyelids (9%) and conjunctiva (7%) were most frequently diagnosed. In cats, it was found that American shorthairs (160; 90%), females (115; 65%) and animals between 1 and 5 years old (74; 42%) were the most affected. In this species, the main eye conditions were those of the cornea (28%), conjunctiva (22%), upper and lower eyelids (22%) and the third eyelid (19%).